2012
DOI: 10.1037/a0026847
|View full text |Cite
|
Sign up to set email alerts
|

Maternal cognitions and mother–infant interaction in postnatal depression and generalized anxiety disorder.

Abstract: Postnatal depression and anxiety have been shown to increase the risk of disturbances in mother–child interaction and child development. Research into mechanisms has focused on genetics and maternal behavior; maternal cognitions have received little attention. Our aim was to experimentally determine if worry and rumination in mothers with generalized anxiety disorder (GAD) and major depressive disorder (MDD), diagnosed in the postnatal 6 months, interfered with maternal responsiveness to their 10-month old inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
129
1
10

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(153 citation statements)
references
References 62 publications
(95 reference statements)
9
129
1
10
Order By: Relevance
“…This is surprising given the hypothesised key role for RNT (in the form of rumination) in mediating the impact of maternal psychopathology on parenting [22]. Stein et al [23, 24] proposed maternal “preoccupation” (including rumination, worry) as a key mechanism that may account for the transmission of psychopathology from a mother to her offspring – highlighting the potential significance of RNT in the postnatal context. There is clearly a need for more research to advance the understanding of how rumination contributes to poor maternal mental health, compromised parenting quality, and impoverished child outcomes [21].…”
Section: Rnt In the Perinatal Contextmentioning
confidence: 98%
See 1 more Smart Citation
“…This is surprising given the hypothesised key role for RNT (in the form of rumination) in mediating the impact of maternal psychopathology on parenting [22]. Stein et al [23, 24] proposed maternal “preoccupation” (including rumination, worry) as a key mechanism that may account for the transmission of psychopathology from a mother to her offspring – highlighting the potential significance of RNT in the postnatal context. There is clearly a need for more research to advance the understanding of how rumination contributes to poor maternal mental health, compromised parenting quality, and impoverished child outcomes [21].…”
Section: Rnt In the Perinatal Contextmentioning
confidence: 98%
“…For example, O’Mahen et al [34] found that high dysphoric postnatal mothers who received a rumination induction demonstrated less effective problem-solving (as well as less confidence in their problem-solving capacity) on a series of parenting-related scenarios relative to those who received a distraction induction, and also to low dysphoric postnatal mothers in both experimental conditions. In another experiment, Stein et al [24] reported that women with post-partum GAD and major depression who received a worry/rumination prime (i.e., instructed to think about a worry or negative thought) were subsequently less responsive to their infant’s vocalisations than those who received a neutral prime (i.e., instructed to think about their journey to the lab). Interestingly, the effect was stronger in mothers with GAD than in those with depression, consistent with our argument about the importance of RNT in the context of anxiety in this population.…”
Section: Potential Roles Of Rnt In the Perinatal Contextmentioning
confidence: 99%
“…[13][14][15][16] Stein and colleagues 17 found that recurrent negative thinking in mothers with GAD resulted in their being less responsive and engaged in interactions with their infants. In addition, these infants appeared to be withdrawn and were more likely to display lowered emotional tone.…”
Section: Consequences Of Gad In Mother and Infantmentioning
confidence: 99%
“…However, prenatal maternal depression (PND) (O'Donnell, Glover, Barker, & O'Connor, 2014;Van Batenburg-Eddes et al, 2013) and maternal post-partum depression (PPD) (Carter, Garrity-Rokous, Chazan-Cohen, Little, & Briggs-Gowan, 2001;Kim-Cohen, Moffitt, Taylor, Pawlby, & Caspi, 2005;Sciberras, Ukoumunne, & Efron, 2011) have also been found related to ADHD and behaviour problems in preschool children. Impaired maternal sensitivity, insecure infant attachment, and less optimal mother-child interactions have been found associated with post-partum depressions (PPD), which may negatively impact on children's further cognitive and behavioural development (Stein et al, 2012a;Carter et al, 2001;Shaw & Vondra, 1995). The increased risk for child symptom development has also been shown equally related to pre-and postnatal exposure to maternal symptoms of anxiety or depression (Giallo, Woolhouse, Gartland, Hiscock, & Brown, 2015;O'Donnell et al, 2014;Carter et al, 2001).…”
Section: Introductionmentioning
confidence: 99%